Occurrence, Phenotypic and Molecular Characterization of Extended-Spectrum- and AmpC- β-Lactamase Producing Enterobacteriaceae Isolated From Selected Commercial Spinach Supply Chains in South Africa - Richter, Loandi; du Plessis, Erika M.; Duvenage, Stacey; Korsten, Lise (Frontiers in Microbiology, 2020)
The increasing occurrence of multidrug-resistant extended-spectrum β-lactamase- (ESBL) and/or AmpC β-lactamase-producing Enterobacteriaceae in health care systems, the environment and fresh produce is a serious concern globally. Production practices, processing and subsequent consumption of contaminated raw fruit and vegetables represent a possible human transmission route. The purpose of this study was to determine the presence of ESBL/AmpC-producing Enterobacteriaceae in complete spinach supply chains and to characterise the isolated strains phenotypically (antimicrobial resistance profiles) and genotypically (ESBL/AmpC genetic determinants, detection of class 1, 2, and 3 integrons). Water, soil, fresh produce and contact surface samples (n=288) from two commercial spinach production systems were screened for ESBL/AmpC-producing Enterobacteriaceae. In total, 14.58 % (42/288) of the samples were found to be contaminated after selective enrichment, plating onto chromogenic media and matrix-assisted laser desorption ionization time-of-flight mass spectrometry identity confirmation of presumptive ESBL/AmpC isolates. This included 15.28 % (11/72) water and 12.12 % (16/132) harvested- and processed spinach, while 25 % (15/60) retail spinach samples were found to be contaminated with an increase in isolate abundance and diversity in both scenarios. Dominant species identified included Serratia fonticola (45.86 %), Escherichia coli (20.83 %), and Klebsiella pneumoniae (18.75 %). In total, 48 (81.36 %) isolates were phenotypically confirmed as ESBL/AmpC-producing Enterobacteriaceae of which 98 % showed a multidrug-resistant phenotype. Genotypic characterisation (PCR of ESBL/AmpC resistance genes and integrons) further revealed the domination of the CTX-M Group 1 ESBL type, followed by TEM and SHV; whilst the CIT-type was the only plasmid-mediated AmpC genetic determinant detected. Integrons were detected in 79.17 % (n=38) of the confirmed ESBL/AmpC-producing isolates, of which we highlight the high prevalence of class 3 integrons, detected in 72.92 % (n=35) of the isolates, mostly in S. fonticola. Class 2 integrons were not detected in this study. This is the first report on the prevalence of ESBL/AmpC-producing Enterobacteriaceae isolated throughout commercial spinach production systems harbouring class 1 and/or class 3 integrons in Gauteng Province, South Africa. The results add to the global knowledge base regarding the prevalence and characteristics of ESBL/AmpC-producing Enterobacteriaceae in fresh vegetables and the agricultural environment required for future risk analysis.